2003
DOI: 10.1136/bjo.87.7.834
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial keratitis: predisposing factors, clinical and microbiological review of 300 cases

Abstract: Aim: To identify predisposing factors and to define clinical and microbiological characteristics of bacterial keratitis in current practice. Methods: A retrospective analysis of the hospital records of patients presenting with bacterial keratitis and treated at the Quinze-Vingts National Center of Ophthalmology, Paris, France, was performed during a 20 month period. A bacterial keratitis was defined as a suppurative corneal infiltrate and overlying epithelial defect associated with presence of bacteria on corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
460
10
26

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 595 publications
(528 citation statements)
references
References 27 publications
32
460
10
26
Order By: Relevance
“…Some studies indicated that immunocompromised status such as diabetes mellitus, [5,11] administration of immunosuppressive agents [11] and HIV infection, [12] are predisposing factors of microbial keratitis. Consequently, we presumed that the immunosuppressive treatment posthematopoietic stem cell transplantation may also increase the risk of infectious keratitis.…”
mentioning
confidence: 99%
“…Some studies indicated that immunocompromised status such as diabetes mellitus, [5,11] administration of immunosuppressive agents [11] and HIV infection, [12] are predisposing factors of microbial keratitis. Consequently, we presumed that the immunosuppressive treatment posthematopoietic stem cell transplantation may also increase the risk of infectious keratitis.…”
mentioning
confidence: 99%
“…This period was less than or equal to 7 days in 69% of cases. In the literature, the average consultation period was 4.6 days in the Netherlands as discussed by Hoddenbach [1], 2 days in France as cited by Bourcier [13] and 5 days in a Moroccan study realized by Benhmidoune and et al [3]. The corneal abscess in our series was unilateral in all cases (100%).…”
Section: Discussionmentioning
confidence: 61%
“…If no laboratory-skilled assistant can be present at the time of sampling, basic microbiologic training should be given to the ophthalmologist, and fresh media should be provided as required. Data showing a rate of definitive diagnosis (70.4%) that is among the highest of those published (1,2,3) are the basis for this encouragement.…”
Section: Investigating Infectious Keratitismentioning
confidence: 99%